Pengaruh Service Quality, Customer Perceived Value, dan Customer Trust Terhadap Customer Loyalty - Al-Qadrie, Muhammad Nur Mi'raj (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Major changes have been made since the outbreak of the COVID-19 pandemic, several companies have collapsed and some have survived and even made profits. Changes in the dynamics of demand for the situation at hand bring new business models developing faster than they should, thus driving significant change. One of the industries affected is online food and one of the concepts is cloud kitchen. This study aims to analyze the effect of service quality, customer perceived value, and customer trust on customer loyalty cloud kitchen Kleise. The questionnaire was used to collect data from users of the Kleise cloud kitchen service with a total of 142 respondents. Data analysis using SPSS from IBM. The results of this study shows there are no influence of service quality variables on customer loyalty and yet the relationship is inversely or negatively related. Conversely, the customer perceived value and customer trust variables show a significant influence with a positive or unidirectional relationship. From the results of this study the authors can provide suggestions to focus on perceived value and trust in running the Kleise cloud kitchen business operations in order to increase customer loyalty. Abstrak Perubahan secara besar dilakukan semenjak terjadinya wabah pandemi COVID-19, ada beberapa perusahaan yang collapse dan ada juga yang bertahan bahkan meraup keuntungan. Perubahan dinamika permintaan aka situasi yang dihadapi membawa model bisnis baru berkembang lebih cepat dari semestinya sehingga mendorong perubahan secara signifikan. Salah satu industri yang terkena dampak adalah online food dan salah satu konsepnya adalah cloud kitchen. Penelitian ini bertujuan untuk menganalisa pengaruh service quality, customer perceived value, dan customer trust terhadap customer loyalty cloud kitchen Kleise. Kuesioner digunakan untuk mengumpulkan data dari pengguna layanan cloud kitchen Kleise dengan total partisipan sebanyak 142 responden. Analisis data menggunakan SPSS dari IBM. Hasil dari penelitian ini adalah tidak adanya pengaruh dari variabel service quality terhadap customer loyalty dan hubungannya berbanding terbalik atau negatif. Sebaliknya variabel customer perceived value dan customer trust menunjukkan pengaruh yang signifikan dengan hubungan positif atau searah. Dari hasil penelitian ini penulis dapat memberikan saran untuk fokus terhadap perceived value dan trust dalam menjalankan operasional usaha cloud kitchen Kleise agar dapat meningkatkan customer loyalty.